Cesarean Section for the Second Twin: A Population‐Based Study of Occurrence and Outcome. Issue 1 (12th March 2013) - Engelbrechtsen, Line; Nielsen, Elise Hoffmann; Perin, Trine; Oldenburg, Anna; Tabor, Ann; Skibsted, Lillian
Abstract Background Although management of twin deliveries has been a topic of discussion for decades, a consensus on how to deliver twins is lacking. The objective of this study was to examine short‐term neonatal outcome of the second twin delivered by cesarean section after vaginal delivery of the first‐born twin (combined delivery) and to identify predictors of combined delivery. Methods This study was a 3‐year, population‐based, retrospective cohort investigation of 1, 254 twin births in Denmark. The twin births were divided into three groups: vaginal deliveries, planned cesarean deliveries, and combined deliveries. Data were extracted from medical records, a fetal medicine software program (Astraia), and the National Birth Registry. Short‐term poor neonatal outcome was measured as a 5‐minute Apgar score ≤ 7, umbilical cord pH ≤ 7.10, and admission to neonatal intensive care unit for more than 3 days. Results Vertex‐nonvertex fetal presentations were more prevalent in combined deliveries than vaginal deliveries (OR 4.4, 2.5–7.8). Nonvertex second twins born by combined delivery had a higher risk of Apgar score ≤ 7 and umbilical cord pH ≤ 7.10 compared with vaginal delivery, unadjusted OR 6.2 (2.1–18), and unadjusted OR 3.9 (1.6–9.5). Prenatal ultrasound scans were evaluated in combined deliveries, of which 48 percent were vertex‐vertex at the last ultrasound scan in pregnancy (mean gestational age 34 + 0) and 37 percent were vertex‐vertex at birth. Conclusions Vertex‐nonvertex presenting twins have an increased risk of combined delivery. Combined deliveries are associated with increased neonatal morbidity for the second twin. (BIRTH 40:1 March 2013)